2022
DOI: 10.30591/smartcomp.v11i2.3536
|View full text |Cite
|
Sign up to set email alerts
|

plikasi Mobile Pendataan Jumantik (Juru Pemantau Jentik) di Rt.005 Rw.001 Kelurahan Jatibening, Kota Bekasi

Abstract: Seiring dengan berkembangnya kemajuan teknologi sekarang ini sangat bermanfaat sekali bagi kita dalam mencari suatu informasi yang begitu cepat, tepat dan akurat yang bisa di akses melalui smartphone, dengan ada kemajuan teknologi dapat membantu kita dalam mengakses informasi dan juga membantu kita dalam menyelesaikan pekerjaan kita sehari-hari. Membuat pekerjaan yang sulit dilakukan menjadi mudah di kerjakan dan mendapatkan hasil yang lebih baik dari sebelumnya. Petugas JUMANTIK (Juru Pemanta Jentik) membutuh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(10 reference statements)
0
2
0
1
Order By: Relevance
“…2, April 2024 memperkirakan produksi peternakan dengan baik [1]. Maka sangan dibutuhkan management pendataan terkait hewan ternak tersebut untuk meningkatkan produksi di peternakan tersebut, memanage data dapat didefenisikan sebagai memetakkan informasi terkait agar informasi tersebut sesuai dengan yang ada dan juga teratur [2][3][4]. Memanage hal tersebut sekaligus melakukan pengawasan hewan ternak dengan seksama itu berdampak meningkatnya kualitas maupun mutu dari ternak tersebut.…”
Section: Pendahuluanunclassified
“…2, April 2024 memperkirakan produksi peternakan dengan baik [1]. Maka sangan dibutuhkan management pendataan terkait hewan ternak tersebut untuk meningkatkan produksi di peternakan tersebut, memanage data dapat didefenisikan sebagai memetakkan informasi terkait agar informasi tersebut sesuai dengan yang ada dan juga teratur [2][3][4]. Memanage hal tersebut sekaligus melakukan pengawasan hewan ternak dengan seksama itu berdampak meningkatnya kualitas maupun mutu dari ternak tersebut.…”
Section: Pendahuluanunclassified
“…17 Other studies revealed that during the Covid-19 pandemic, periodic larvae inspections were almost not carried out, after the development of a mobile application, data collection by Jumantik increased again, reaching 90% in carrying out periodic larvae inspections. 11 The Si-DBD application will make it easier for households in the process of checking and reporting the results of activities, from previously carrying out inspections and recording them manually on paper, then having to store and be responsible for the data before the jumantik coordinator visits and recaps the results of inspections by households.…”
Section: Periodic Larvae Examinationmentioning
confidence: 99%
“…Research by Akbar, namely the development of the M-Jumantik mobile application facilitates coordination between the community and Jumantik puskesmas officers in conducting periodic larva monitoring during the Covid-19 pandemic. 11 Research by Sugeng et al, in the development of a webpagebased Jumantik information system (Simpatik) at the puskesmas, can maximize the accuracy of information and save time in preparing reports. 12 Based on the results of research that has been done previously that the use of applications related to DHF and in particular the implementation of larva monitoring is already available, but it is still complicated to use for the general public because the application is aimed only at trained larvae and puskesmas officers.…”
Section: Introductionmentioning
confidence: 99%